(untitled) (Journal of economic and management development research, 2025)
Based on the《2020 China Input-Output Table》, this paper constructs a complete consumption coefficient matrix for the textile and apparel industry and analyzes its regulatory implications from the perspective of economic law. The study reveals that this matrix not only uncovers the structural dependence of the apparel industry on upstream raw material sectors but also serves as a legal basis for identifying the transmission of market dominance, industrial chain vulnerabilities, joint environmental responsibilities, and product quality traceability. Accordingly, this paper proposes expanding the definition of "dependent dominance" in antitrust law, using high complete consumption relationships as a quantitative benchmark for industrial chain security reviews, and establishing environmental co-governance and product liability penetration mechanisms based on the complete consumption coefficient. These recommendations provide empirical support and pathway guidance for the precise implementation of economic law in complex industrial chains.